ENVELHECIMENTO DA FORÇA DE TRABALHO DO GOVERNO FEDERAL: DESAFIOS PARA A EDUCAÇÃO SUPERIOR PÚBLICA - Júlio Eduardo Ornelas Silva; Cláudio José Amante; Luiz Salgado Klaes; Marilda Todescat; Eduardo Lobo (Revista Gestão Universitária na América Latina, 2012)
Population aging is a worldwide trend that has accelerated since the eighteenth century, beginning with the Industrial Revolution. It is characterized by two primary factors: declining birth rate and declining death rate. Developed and socioeconomically mature countries are at an advanced stage in the population aging, while developing countries tread the same path. This article aims to analyze the stage of workforce aging of the Ministry of Education - MEC, through research documents that portray the situation in the last ten years of this public agency that has the largest amount of workers in the Union. The results indicate that the stage of workforce aging of the MEC is not advanced, although the costs of social security are growing. However, under a long-term perspective, to achieve the goals desired by the government for higher education, changes of attitude by public managers are necessary.